Hubungan antara kepimpinan transformasional guru besar dengan kepuasan kerja guru - Felicia, Ann; Sin, Ishak (Bahagian Pendidikan Guru, 2012)
The purpose of this study was to determine the relationships between headmaster's transformational leadership and teachers' job satisfaction among the selected school.The study also seeks to determine the level of headmaster's transformational leadership and the level of teachers 'job satisfaction.The cross-sectional survey method using standardized-item questionnaires was employed in this study.The respondents consisted of 118 teachers were chosen randomly from 13 schools area Tebedu, Serian, Sarawak.The Transformational Leadership Survey Questionnaire by Griffith 2003 was used to measure the dimensions of transformational leadership and the dimensions of teachers' job satisfaction.Five null hypotheses were generated and tested using Pearson correlation, t-test and ANOVA.The findings and the implications showed that there was a positive significant relationship between headmaster's transformational leadership and teachers' job satisfaction.The results showed that the headmaster's transformational leadership is in the high level as well as teachers' job satisfaction level.However, the results showed that there are differences of job satisfaction level between male and female teacher, and between difference ages.In spite of that, there is no difference of job satisfaction level between teachers 'marital status and employment status.